Automatic Noise Gate Settings for Drum Recordings Containing Bleed from Secondary Sources. (16th February 2011) - Terrell Terrell, Michael Michael; Reiss Reiss, Joshua D. Joshua D.; Sandler Sandler, Mark Mark
Abstract : An algorithm is presented which automatically sets the attack, release, threshold, and hold parameters of a noise gate applied to drum recordings which contain bleed from secondary sources. The gain parameter which controls the amount of attenuation applied when the gate is closed is retained, to allow the user to control the strength of the gate. The gate settings are found by minimising the artifacts introduced to the desirable component of the signal, whilst ensuring that the level of bleed is reduced by a certain amount. The algorithm is tested on kick drum recordings which contain bleed from hi-hats, snare drum, cymbals, and tom toms.